Blood Relations, Broken Rights: Mediation as a Socio-Legal Mechanism in Heirs’ Land Ownership and Control Disputes in Indonesia - Norafiq Aldyan; Dian Latifiani; Nur Arif Nugraha (Universitas Negeri Semarang, 2024)
Inheritance-related land disputes in Indonesia remain a persistent legal and social issue due to the country’s pluralistic legal system, which integrates statutory law, customary (adat) law, and Islamic inheritance principles. This study examines the role of mediation as an alternative dispute resolution mechanism in resolving conflicts over heirs’ land ownership and control rights. It emphasizes mediation as both a procedural legal instrument and a socio-legal approach that accommodates family values and local wisdom in dispute settlement. Using doctrinal and socio-legal methods, the study analyzes Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution and Supreme Court Regulation (PERMA) No. 1 of 2016 on Court-Annexed Mediation, alongside their application in inheritance land disputes. Findings indicate that conflicts among heirs arise from unclear inheritance distribution, overlapping claims, and tensions between formal legal norms and customary practices, often escalating into litigation with prolonged uncertainty and weakened family relations. The study finds that mediation provides a flexible, efficient, and restorative alternative to adversarial litigation. It enables parties to reach mutually agreed settlements that ensure legal certainty and preserve social harmony, reflecting Indonesian dispute resolution values. Challenges remain regarding mediator competence, enforcement of agreements, and varying acceptance across legal traditions. This study contributes to Indonesian legal scholarship by offering a socio-legal analysis of mediation in inheritance land disputes and its role in harmonizing state, customary, and Islamic laws. For a global audience, it provides insights into how legal pluralism shapes dispute resolution in non-Western contexts, offering lessons for comparative studies of alternative dispute resolution and hybrid legal systems.